Economic Development of Regions Based on Promoting Small Business and Private Entrepreneurship in the Context of Transition to a Green Economy (KIUT Publication, 2025)
This article examines the development of small businesses and private entrepreneurship in the context of transitioning to a green economy. The main principles of the green economy and its role in regional economic development are analyzed. The author proposes mechanisms to ensure environmental safety and support economic growth by incentivizing small business entities. Additionally, the article discusses the opportunities for small entrepreneurship to implement environmentally oriented innovations, the contribution of the private sector to regional development, and provides recommendations for addressing existing challenges.